Pain Measurement in Mechanically Ventilated Patients After Cardiac Surgery: Comparison of the Behavioral Pain Scale (BPS) and the Critical-Care Pain Observation Tool (CPOT). Issue 5 (October 2017) - Rijkenberg, S.; Stilma, W.; Bosman, R. J.; van der Meer, N. J.; van der Voort, P. H. J.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 31:1227–1234, 2017) Postsurgical pain is common in critically ill patients, such as cardiac surgery patients, and can have a negative effect on recovery. The experience of severe pain during intensive care unit (ICU) stays has been linked to the development of posttraumatic stress disorder–related symptoms.